Prevalence of Familial Hypercholesterolemia Among the General Population and Patients With Atherosclerotic Cardiovascular Disease: A Systematic Review and Meta-Analysis. Issue 22 (2nd June 2020) - Hu, Pengwei; Dharmayat, Kanika I.; Stevens, Christophe A.T.; Sharabiani, Mansour T.A.; Jones, Rebecca S.; Watts, Gerald F.; Genest, Jacques; Ray, Kausik K.; Vallejo-Vaz, Antonio J.
Abstract : Background: Contemporary studies suggest that familial hypercholesterolemia (FH) is more frequent than previously reported and increasingly recognized as affecting individuals of all ethnicities and across many regions of the world. Precise estimation of its global prevalence and prevalence across World Health Organization regions is needed to inform policies aiming at early detection and atherosclerotic cardiovascular disease (ASCVD) prevention. The present study aims to provide a comprehensive assessment and more reliable estimation of the prevalence of FH than hitherto possible in the general population (GP) and among patients with ASCVD. Methods: We performed a systematic review and meta-analysis including studies reporting on the prevalence of heterozygous FH in the GP or among those with ASCVD. Studies reporting gene founder effects and focused on homozygous FH were excluded. The search was conducted through Medline, Embase, Cochrane, and Global Health, without time or language restrictions. A random-effects model was applied to estimate the overall pooled prevalence of FH in the general and ASCVD populations separately and by World Health Organization regions. Results: From 3225 articles, 42 studies from the GP and 20 from populations with ASCVD were eligible, reporting on 7 297 363 individuals/24 636 cases of FH and 48 158 patients/2827 cases of FH, respectively. More than 60% of the studies were from Europe. Use of the Dutch Lipid Clinic Network criteria was the commonest diagnostic method. Within the GP, the overall pooled prevalence of FH was 1:311 (95% CI, 1:250–1:397; similar between children [1:364] and adults [1:303], P =0.60; across World Health Organization regions where data were available, P =0.29; and between population-based and electronic health records–based studies, P =0.82). Studies with ⩽10 000 participants reported a higher prevalence (1:200–289) compared with larger cohorts (1:365–407; P <0.001). The pooled prevalence among those with ASCVD was 18-fold higher than in the GP (1:17 [95% CI, 1:12–1:24]), driven mainly by coronary artery disease (1:16; [95% CI, 1:12–1:23]). Between-study heterogeneity was large ( I 2 >95%). Tests assessing bias were nonsignificant ( P >0.3). Conclusions: With an overall prevalence of 1:311, FH is among the commonest genetic disorders in the GP, similarly present across different regions of the world, and is more frequent among those with ASCVD. The present results support the advocacy for the institution of public health policies, including screening programs, to identify FH early and to prevent its global burden. Abstract : Supplemental Digital Content is available in the text.